Association of ultrasound signs of sarcopenia with serum ferritin levels and hepatic indices like NFS and FIB-4 in NAFLD patients - Bahar Arasteh; Sina Hamzehzadeh; Kia Seyed Toutounchi; Zeinab Nikniaz; Leila Amini; Leila Alizadeh (BMC Gastroenterology)
Abstract Introduction Non-alcoholic fatty liver disease is one of the most common chronic diseases all around the world, which significantly correlates with metabolic disorders and inflammatory cycles. Sarcopenia is a decrease in the mass of skeletal muscles interacting with factors such as inflammatory processes and chronic diseases. It can also lead to the aggravation of chronic diseases. Method The study population was randomly selected and entered into the research based on exclusion and inclusion criteria. Non-alcoholic fatty liver disease was confirmed in all members of the study population by ultrasound. Patients’ serum ferritin level was assessed, and their NFS and Fib 4 scores were calculated. Sarcopenia was diagnosed by measuring the thickness of the rectus femoris by ultrasonography. The correlation between these variables was evaluated and analyzed by statistical software. Results According to statistical analysis, there is a significant association between the serum ferritin level and sarcopenia (P-value < 0.001). Besides, there is a significant association between NFS, Fib4, and sarcopenia (P-value = 0.024, 0.000). Conclusion This research’s results reflect the correlation between serum ferritin and sarcopenia; however, it cannot conclude a cause-and-effect relationship between these variables.